The Implementation of Human Resource Accounting in Indonesia: A Bibliometric Analysis - Erwin Indriyanto; Molina; Muhammad Nur; Kumba Digdowiseiso; Wan Zuriati Wan Zakaria (CV ODIS, 2023)
Human Resources (HR) refers to the assets of a company or organization. The role of this asset is realized in the form of innovative, skilled, and creative thoughts and energy so that it can increase performance efficiency and effectiveness and take the company or organization in a more advanced direction. Human resources information must be presented informatively and communicatively. One way to do this is through human resource accounting. Therefore, a study is needed on the application of human resource accounting in Indonesia. The method used is bibliometric analysis with clustering and density. This research also tries to review the main themes raised in the study topic, to make it easier for the author to classify themes in the analysis. Based on the findings of this research, it is known that the keyword that appears most frequently is